Der Mehrwert Komparativer Theologie für eine die Pluralität ernst nehmende Religionspädagogik - Kamcili-Yildiz, Naciye; Tautz, Monika (Dialog und Transformation. Auf dem Weg zu einer pluralistischen Religionspädagogik)

„Andere Religionen“ in den Curricula der islamischen Religionslehrerausbildung - Kamcili-Yildiz, Naciye (Theo-Web. Zeitschrift für Religionspädagogik)

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

Qur’anic Intertextuality with Jewish-Rabbinic Tradition: the Case of ‘the Cow’ in Q 2:67-74 - Aghaei Abrandabadi, Seyed Ali (Reading the Bible in the Context of Islam)

The Common Link and its Relation to the Hadith Terminology - Aghaei Abrandabadi, Seyed Ali (Modern Hadith Studies: Continuing Debates and New Approaches)

Zuordnungsverfahren für Tauschbörsen - N., N.

Bilder verstehen – Bilder gebrauchen (Modul 4) - Blachut, Alisa (Deutsch lernen: Sprechen – Zuhören – Lesen – Schreiben. DaM – DaZ – DaF. Arbeitsheft 2)

Schutte, Valerie / Paranque, Estelle: Forgotten Queens in Medieval and Early Modern Europe. Political Agency, Myth-Making, and Patronage - Foerster, Anne (Das Mittelalter)

Kane, Bronach C: Popular Memory and Gender in Medieval England. Men, Women and Testimony in the Church Courts, c.1200–1500 - Foerster, Anne (H-Soz-Kult)

Drews, Wolfram: Die Interaktion von Herrschern und Eliten in imperialen Ordnungen des Mittelalters - Foerster, Anne (DA)

Systematische Wahl einer Modellierungstiefe im Entwurfsprozess mechatronischer Systeme - Lochbichler, Matthias

Lebensdauerprognose für additiv gefertigte Kunststoffbauteile mittels bruchmechanischer Konzepte - Bauer, Benjamin

In Zeiten von p-hacking und fake science: Wissenschaftsorientierung als Herausforderung an die Psychologiedidaktik - Scharlau, Ingrid; Schreiber, Christine (Psychologie unterrichten in Deutschland, Österreich und der Schweiz: Leitlinien und Grundlagen)
Keywords: Unterrichtsfach Psychologie

Psychologiedidaktik durch Kommunikationsanalyse - Scharlau, Ingrid; Schreiber, Christine; Patrzek, Justine (Psychologiedidaktik und Evaluation XIII)
Keywords: Unterrichtsfach Psychologie

Towards Quantum One-Time Memories from Stateless Hardware - Broadbent, Anne; Gharibian, Sevag; Zhou, Hong-Sheng (Proceedings of the 15th Conference on the Theory of Quantum Computation, Communication and Cryptography (TQC))
A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum settings. Here, we propose a scheme for using quantum information, together with the assumption of stateless (i.e., reusable) hardware tokens, to build statistically secure OTMs. Via the semidefinite programming-based quantum games framework of Gutoski and Watrous [STOC 2007], we prove security for a malicious receiver, against a linear number of adaptive queries to the token, in the quantum universal composability framework. We prove stand-alone security against a malicious sender, but leave open the question of composable security against a malicious sender, as well as security against a malicious receiver making a polynomial number of adaptive queries. Compared to alternative schemes derived from the literature on quantum money, our scheme is technologically simple since it is of the "prepare-and measure" type. We also show our scheme is "tight" according to two scenarios.

On efficiently solvable cases of Quantum k-SAT - Gharibian, Sevag; Aldi, Marco; de Beaudrap, Niel; Saeedi, Seyran (Communications in Mathematical Physics)

Communication and Capitalism. A Critical Theory - Fuchs, Christian

Marxism. Karl Marx’s Fifteen Key Concepts for Cultural and Communication Studies. Key Ideas in Media & Cultural Studies Series - Fuchs, Christian

Nationalism on the Internet: Critical Theory and Ideology in the Age of Social Media and Fake News - Fuchs, Christian

Towards a Critical Theory of Communication as Renewal and Update of Marxist Humanism in the Age of Digital Capitalism - Fuchs, Christian (Journal for the Theory of Social Behaviour)

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Marx heute. Eine Einführung in die kritische Theorie der Kommunikation, der Kultur, der digitalen Medien und des Internets - Fuchs, Christian

Kommunikation und Kapitalismus. Eine kritische Theorie - Fuchs, Christian

Alltagsleben und Alltagskommunikation im Coronavirus-Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Everyday Life and Everyday Communication in Coronavirus Capitalism - Fuchs, Christian (tripleC: Communication)

The Utopian Internet, Computing, Communication, and Concrete Utopias - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Erich Fromm and the Critical Theory of Communication - Fuchs, Christian (Humanity & Society)

The Ethics of the Digital Commons - Fuchs, Christian (Journal of Media Ethics)

Sosyal Medya: Eleştirel Bir Giriş - Fuchs, Christian

Beitrag zur Steigerung der Qualität von Aluminium-Lichtbogen-Bolzenschweißverbindungen mit Hubzündung - Hader, Christoph

Ersatzmodellentwicklung zur Prognose des kerbinduzierten Fügeteilversagens von Halbhohlstanznietverbindungen unter Crashbelastung - Porsch, Tony

Entwicklung des Prägeelementschweißens für Aluminium-Stahl-Verbindungen im Karosseriebau - Pietsch, Tommy

Qualifizierung intelligenter Datenanalysemethoden bei vollautomatisierten Klebtechnikanwendungen - Sierak, Paulina

Entwicklung einer Methodik zur numerischen Simulation des Hochgeschwindigkeits-Bolzensetzens - Gerkens, Michael

Imaginary quadratic number fields with class groups of small exponent - Elsenhans, Andreas-Stephan; Klüners, Jürgen; Nicolae, Florin (Acta Arithmetica)
Let D<0 be a fundamental discriminant and denote by E(D) the exponent of the ideal class group Cl(D) of K=ℚ(√D). Under the assumption that no Siegel zeros exist we compute all such D with E(D) dividing 8. We compute all D with |D| ≤ 3.1⋅10²⁰ such that E(D) ≤ 8.
Keywords: Algebra and Number Theory

The conductor density of local function fields with abelian Galois group - Klüners, Jürgen; Müller, Raphael (Journal of Number Theory)
We give an exact formula for the number of G-extensions of local function fields Fq((t)) for finite abelian groups G up to a conductor bound. As an application we give a lower bound for the corresponding counting problem by discriminant.
Keywords: Algebra and Number Theory

Modellierung des Strömungs- und Trennverhaltens viskoser Gemische in Packungskolonnen basierend auf tomographischen Untersuchungen - Große Daldrup, Anna

数字时代的资本主义、父权制、奴隶制与种族主义 - Fuchs, Christian (国外社会科学前沿 (Studies on Foreign Social Sciences))

Interview mit Christian Fuchs: »Der Sozialismus ist keine App und kann nicht aus dem Internet heruntergeladen werden«. Marx’ Vision der befreiten Gesellschaft bleibt im digitalen Zeitalter aktuell - Fuchs, Christian (Das Argument)

Vida e comunicação cotidianas no capitalism da coronavirus - Fuchs, Christian (MATRIZes)

Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Neuroscience)
Keywords: General Neuroscience

Ethik-Briefing. Leitfaden für eine verantwortungsvolle Entwicklung und Anwendung von KI-Systemen - Matzner, Tobias; Heesen, Jessica; Grundwald, Armin; Roßnagel, Alexander (der Plattform Lernende Systeme)

Digital ist anders — Über eine Universität ohne Präsenzlehre - Matzner, Tobias (Medium.com)

Mediensucht? Über die Medikalisierung der Mediennutzung in Suchtdebatten - Matzner, Tobias (Die dunklen Seiten des Konsums – Alte Probleme, neue Herausforderungen)

Feed the Interface – Social-Media-Feeds und filternde Schwellen - Schulz, Christian; Matzner, Tobias (Navigationen)

Investigation of the Surface Equivalence Principle on a Metal Surface for a Near-Field to Far-Field Transformation by the NFS3000 - Lange, Sven; Schroder, Dominik; Hedayat, Christian; Hangmann, Christian; Otto, Thomas; Hilleringmann, Ulrich (2020 International Symposium on Electromagnetic Compatibility - EMC EUROPE)

27th European Solid-State Device Research Conference - Hilleringmann, Ulrich

Designing Mixed-Signal PLLs regarding Multiple Requirements taking Non-Ideal Effects into Account - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))

Inductive Locating Method to Locate Miniaturized Wireless Sensors within Inhomogeneous Dielectrics - Lange, Sven; Schroder, Dominik; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

Je höher qualifiziert, desto besser? Rezeptive Phrasemkompetenzen von Französischlernenden

Das Smartphone in der berufsvorbereitenden Bildung junger Erwachsener. Empirische Erkundungen aus praxistheoretischer Perspektive - Dehmel, Lukas; Zick, Sebastian (Praxistheoretische Perspektiven in der Medienpädagogik)

Medienpädagogisches Erwachsenenbildungspersonal und Mediatisierung. Konzeptionelle Überlegungen zur theoretischen Erfassung biografischer Bearbeitungsprozesse - Dehmel, Lukas (Zeitschrift MedienPädagogik 37)

Vergissmeinnicht! Self-Tracking-Apps auf dem Smartphone als Erinnerungsräume junger Erwachsener - Dehmel, Lukas; Burgfeld-Meise, Bianca (MerzWissenschaft)

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Early stage crack detection in mechanically joined steel/aluminum joints by condition monitoring - Gollnick, Maik; Giese, Patrick; Hein, David; Meschut, Gerson; Herfert, Daniel (Materials Testing)
Monitoring systems for machines, plants, materials and equipment are increasingly used in production processes. These online condition monitoring systems can detect damage or excessive loads at an early stage and can drastically reduce or prevent long downtimes of plants and machines as well as high repair and maintenance costs. This paper depicts a method for online crack detection with pattern recognition methods for specimens joined by self-pierce riveting under cyclic load in fatigue tests (laboratory application). A software specially conceived for this application was developed. This software, AnrissMF, uses active acoustic testing with a structure-borne sensor to detect cracks in the joints at a very early stage. It is shown in this paper that this software can detect cracks much earlier than classical failure criteria for joints (i. e. before any drop in stiffness or frequency is observed). Furthermore, the successful application of software AnrissMF for online crack detection during the fatigue strength test is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Raczkowski, Felix; Shnayien, Mary; Weich, Andreas; Wippich, Uwe
Die Autor*innen werfen einen medienwissenschaftlichen Blick auf die Online-Lehre des Sommersemsters 2020. Dabei betrachten sie unter anderem den Unterschied von klassischen Hörsälen zu den neuen, virtuellen Lernräumen, die aber auch physische Elemente beinhalten. Dabei regen sie an, den Einsatz von Lehr-Lern-Plattformen kritisch zu diskutieren und insgesamt die Lehre mit andauernder Medienreflexion zu begleiten. Ein zentraler Punkt des Papiers ist das Aufzeigen von Inklusions- und Exklusionspotenzialen von Online-Lehre. Vermeintliche Selbstverständnisse spielen hier eine Schlüsselrolle. So wird zum Beispiel häufig eine gewisse technische Infrastruktur seitens der Studierenden vorausgesetzt, die nicht immer vorhanden ist. Andererseits entfallen physische Barrieren, die in Lehrgebäuden vorhanden wären. Die Autor*innen mahnen, bei der Konzeption von Online-Lehre zu vermeiden, nicht-behinderte Personen als die Norm anzunehmen und stattdessen von verschiedenen Körperlichkeiten her zu denken, um die positive Potenziale dieses Lehrmodus zu nutzen. Das Diskussionspapier widmet sich auch ausführlich dem Einsatz von (digitalen) Tools, die weniger als Werkzeuge, denn als Medien der Lehre verstanden werden.

Lehre unter besonderen Bedingungen. Leitfaden zur temporären Umstellung der Lehre auf Online-Formate - Heinke, Christian; Shnayien, Mary; Sprenger, Florian; Wippich, Uwe (-)
Die vorübergehende Umstellung der Lehre von Präsenz- auf alternative Formate (sowohl online als auch offline) ist nicht nur eine logistische Herausforderung, sondern hat auch eine medientheoretische und eine wissenschaftspolitische Dimension. Gerade als Medienwissenschaftler_innen sollten wir in dieser Hinsicht reflektiert vorgehen, denn wir haben es mit einer Frage der Übersetzbarkeit von Inhalten zwischen unterschiedlichen Medien zu tun. Der Versuch, Lehrinhalte vom Medium des Sprechens und Diskutierens vor Ort in das Medium etwa einer Konferenzschaltung oder einer kollaborativen schriftlichen Textkommentierung zu übersetzen, verändert diese Inhalte. Wenn wir neue Formate für die Lehre unter besonderen Bedingungen ausprobieren, sollten wir uns die medienwissenschaftliche Prämisse, dass das Medium die Botschaft ist, ständig vor Augen halten. Deshalb schlagen wir vor, diese Aufgabe als ein medienwissenschaftliches Experiment zu betrachten und dieses Experiment im kommenden Semester nicht nur zum Medium, sondern auch zum Inhalt unserer Seminare zu machen.

Explorations in Digital Cultures
Digital media are transformative: they (re)shape the ways of communicating, relating, doing, knowing, and living as much as they are themselves subject to continuous transformation. The contributions in this volume explore these contemporary shifts in and of digital cultures by analyzing a wide range of topics: from data, infrastructures, algorithms, logistics, economies, politics, identities, collectives […] It’s Open Access! Check it out!

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf. - Heisler, Dietmar; Schemmer, Susanne (BWP@ Berufs- und Wirtschaftspädagogik - online)
Jugend wird als eine eigenständige Lebens- und Entwicklungsphase betrachtet. Für junge Geflüchtete stellt sie eine besondere Herausforderung dar. Für sie geht es nicht nur um die Bewältigung alterstypischer Entwicklungsaufgaben, sondern auch um eine gelingende Integration in die Aufnahmegesellschaft. Dazu gehören u. a. das Kennenlernen und die Aneignung von Sprache, Kultur und Werten, genauso die Erschließung von Alltagsräumen und Lebenswelten, z. B. von Freizeitmöglichkeiten, Bildung und von beruflichen Erfahrungsräumen. Die Frage zur gelingenden Integration und Gestaltung von Lebenswelten junger Geflüchteter wurde im Kontext der wissenschaftlichen Begleitung des Projekts „angekommen in Deiner Stadt“ der Walter Blüchert Stiftung genauer untersucht. Der Beitrag referiert u. a. die Ergebnisse einer in diesem Kontext durchgeführten egozentrierten Netzwerkanalyse. Die Ergebnisse zeigen, dass die Angebote den Rahmen für den Aufbau und die Erweiterung kommunikativer, sozialer Netzwerke darstellen und lebensweltliche Zugänge öffnen.
Keywords: Jugend; Lebensweltorientierung; soziale Netzwerke; geflüchtete Jugendliche; Lebenslagen junger Geflüchteter und Zugewanderter

Digitalisierung der Berufs- und Arbeitswelt. Herausforderungen und Potenziale in der Aus- und Weiterbildung für Geringqualifizierte, Un- und Angelernte - Heisler, Dietmar (Digitalisierung über berufliche Bildung gestalten.)
„Digitalisierung“ und die oft analog benutzten Begriffe „Industrie 4.0“, „Arbeit 4.0“ usw., gelten als zentrale, aktuelle Entwicklungen in Deutschland. Gemeint ist damit der Einzug moderner Informations- und Kommunikationstechnologien, insbesondere des Computers, des Internets, von funkbasierten Überwachungssystemen, Steuerungs- und Netzwerktechnologien, z.B. RFID und Bluetooth, von mobilen Technologien bzw. Endgeräten usw., in die Berufs- und Arbeitswelt, in Dienstleistung und Produktion. Begleitet wird dies durch eine zunehmende Miniaturisierung von Technologien, die Ausstattung von Gegenständen mit einer eigenen Intelligenz (smart products) und die Vernetzung dieser Gegenstände zu cyber-physischen Systemen (CPS). Der Beitrag befasst sich mit der Frage, welche Potenziale, aber auch welche Risiken der digitale Wandel sowie die Digitalisierung von Aus- und Weiterbildung für Menschen birgt, die am Arbeitsmarkt als Geringqualifizierte, als Un- und Angelernte gelten. Es wird davon ausgegangen, dass gerade diese Menschen vom digitalen Wandel in besonderem Maße betroffen sein werden. Es ist zu erwarten, dass es durch den digitalen Wandel zu neuen Segmentierungen, zu neuen Ausschluss- und Benachteiligungsmechanismen kommt, von denen Geringqualifizierte und auch andere marginalisierte und benachteiligte Menschen am Arbeitsmarkt und in der beruflichen Bildung betroffen sein werden. Der Aus- und Weiterbildung wird eine besondere Bedeutung beigemessen, um diesen Menschen die Teilhabe und Mitgestaltung des digitalen Wandels zu ermöglich.
Keywords: Digitalisierung; Geringqualifizierte; Weiterbildung; Un- und Angelernte

Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung

RESIlienz durch Helfernetzwerke zur BEwältigung von KriSen und Katastrophen - RESIBES : Schlussbericht zum Verbundprojekt : Teilvorhaben: Entwicklung und Bewertung von kommunikativen und organisatorischen Verfahren zur Etablierung eines Helfernetzwerkes - Hälterlein, Jens

Die Prognose sicherheitsrelevanter Ereignisse mittels Künstlicher Intelligenz. Zukunftsvorstellungen, Erwartungen und Effekte auf Praktiken der Versicherheitlichung - Hälterlein, Jens (BEHEMOTH. A Journal on Civilisation)

"Manche wissen halt einfach echt nicht, wie Studieren funktioniert, hat man das Gefühl" - Kontextuelle Dimensionen und Orientierungen studentischen Medienhandelns - Mojescik, Katharina; Engemann, Mario; Limpinsel, Inga; Lewandowski, Kira; Aßmann, Sandra (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

ABC: ABseits des Curriculums - Non-formales und informelles Lernen ab dem 1. Semester forschend erfassen - Aßmann, Sandra; Steffens, Yannic; Engemann, Mario; Blome, Andrea (Forschendes Lernen an Universitäten. Prinzipien, Methoden, Best Practices an der Ruhr-Universität Bochum)

Die Erforschung studentischen Medienhandelns mit der dokumentarischen Methode. Forschungsleitende Grundannahmen und forschungspraktische Umsetzung - Pensel, Sabrina; Mojescik, Katharina; Aksoy, Filiz; Engemann, Mario; Lewandowski, Kira (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

All-in-One - Hochschulkontexte studiengerecht und digital gestalten durch einen ganzheitlichen Onboarding-Prozess - Limpinsel, Inga; Neuberger, Olga; Aßmann, Sandra; Engemann, Mario (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

Einbindung Studierender bei der Erforschung studentischen Medienhandelns - Mojescik, Katharina; Pensel, Sabrina; Schick, Sarah; Engemann, Mario (Studierende - Medien - Universität. Einblicke in studentische Medienwelten)

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi V.; Wilhelm, René; Schmidt, Wolf G. (Journal of Computational Chemistry)

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Vibrational Raman spectroscopy on adsorbate-induced low-dimensional surface structures - Speiser, Eugen; Esser, Norbert; Halbig, Benedikt; Geurts, Jean; Schmidt, Wolf Gero; Sanna, Simone (Surface Science Reports)

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Molecular doping in few-molecule polymer-dopant complexes shows reduced Coulomb binding - Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Coulomb binding energy is reduced when a few-molecule integer charge transfer complex (ICTC) is formed.
Keywords: Materials Chemistry; General Chemistry

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Externally controlled Lotka-Volterra dynamics in a linearly polarized polariton fluid - Pukrop, Matthias; Schumacher, Stefan (Physical Review E)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures - Aldahhak, Hazem; Powroźnik, Paulina; Pander, Piotr; Jakubik, Wiesław; Dias, Fernando B.; Schmidt, Wolf Gero; Gerstmann, Uwe; Krzywiecki, Maciej (The Journal of Physical Chemistry C)

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carrier-wave population transfer in semiconductors - Zuo, R; Song, X; Meier, Torsten; Yang, W (Journal of Physics: Conference Series)

Investigation of influencing parameters on the joint formation of the self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Lechner, Michael; Bobbert, Mathias; Meschut, Gerson; Merklein, Marion

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)